2000
DOI: 10.1073/pnas.050587197
|View full text |Cite|
|
Sign up to set email alerts
|

Activation of antitumor cytotoxic T lymphocytes by fusions of human dendritic cells and breast carcinoma cells

Abstract: We have reported that fusions of murine dendritic cells (DCs) and murine carcinoma cells reverse unresponsiveness to tumor-associated antigens and induce the rejection of established metastases. In the present study, fusions were generated with primary human breast carcinoma cells and autologous DCs. Fusion cells coexpressed tumor-associated antigens and DC-derived costimulatory molecules. The fusion cells also retained the functional potency of DCs and stimulated autologous T cell proliferation. Significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
109
1
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 189 publications
(115 citation statements)
references
References 24 publications
4
109
1
1
Order By: Relevance
“…In this approach, TAAs, including both known and unidentified Ags are delivered to DCs, processed, and presented through both MHC class I and II pathways in the context of costimulatory molecules (6). We have previously reported that immature (Imm) DCs (Imm-DCs) fused with autologous tumor cells can induce Ag-specific polyclonal CTLs in vitro (7)(8)(9)(10)(11). Although immunization with DC/tumor cell FCs in patients with cancer has been associated with immunological responses in phase I clinical trials, early clinical trials have shown only limited success (12)(13)(14)(15)(16)(17).…”
Section: Synergistic Induction Of Antigen-specific Ctl By Fusions Of mentioning
confidence: 99%
“…In this approach, TAAs, including both known and unidentified Ags are delivered to DCs, processed, and presented through both MHC class I and II pathways in the context of costimulatory molecules (6). We have previously reported that immature (Imm) DCs (Imm-DCs) fused with autologous tumor cells can induce Ag-specific polyclonal CTLs in vitro (7)(8)(9)(10)(11). Although immunization with DC/tumor cell FCs in patients with cancer has been associated with immunological responses in phase I clinical trials, early clinical trials have shown only limited success (12)(13)(14)(15)(16)(17).…”
Section: Synergistic Induction Of Antigen-specific Ctl By Fusions Of mentioning
confidence: 99%
“…Monocyte derived DCs were generated as described [24]. Briefly, PBMCs were isolated on lymphoprep (1.077 g/ml Nycomed Pharma Oslo Norway) resuspended in CM supplemented with 10% AB serum and cultured in T25 flask for 2 hours at 37˚C, The nonadherent cells were then removed and used for T cell enrichment by nylon wool, the adherent cells were cultured in CM containing GM-CSF and IL-4 at final concentrations of 1000 U/ml and 800 U/ml respectively.…”
Section: Generation Of Tumor Cell Lysate Pulsed DCmentioning
confidence: 99%
“…Most cancer cells are poor immunogens due to the lack of costimulatory element B7 or the downregulation of MHC class I expression, both of which are essential for activation of T cells (Gong et al, 2000). Therefore, cancer cells do not activate the T-cell response.…”
mentioning
confidence: 99%